P200 Characterisation of remission in patients with rheumatoid arthritis treated with upadacitinib or comparators. (20th April 2020) - Hall, Stephen; Takeuchi, Tsutomu; Thomson, Glen; Emery, Paul; Combe, Bernard; Everding, Andrea; Pavelka, Karel; Song, Yanna; Shaw, Tim; Friedman, Alan; Song, In-Ho; Mysler, Eduardo
Abstract: Background: Across all phase 3 studies, treatment with upadacitinib (UPA), a JAK1-selective inhibitor, was associated with significantly higher remission (REM) rates, compared to placebo (PBO) or active comparators, in RA patients who were methotrexate (MTX)-naive, had inadequate response to conventional synthetic (csDMARD-IR) or had inadequate response or intolerance to biologic DMARDs (bDMARD-IR). Methods: REM definitions are based on composite scores of various individual assessments of disease activity. To determine the response to UPA on REM and component assessments, we assessed the proportions of patients achieving REM using multiple REM definitions, and the improvement in their respective individual components, compared to PBO or active comparators, in 3 different RA patient populations spanning a range of RA patient populations. Methods: Three phase 3 studies included patients who were MTX naïve (SELECT EARLY, n = 945), MTX-IR (SELECT COMPARE, n = 1629) and bDMARD-IR (SELECT BEYOND, n = 498). The proportion of patients achieving REM at Week 12 by 4 definitions (DAS28-CRP<2.6; CDAI <2.8; SDAI <3.3 and Boolean, defined as < 1 for TJC, SJC, patient's global assessment of disease activity [PtGA], and CRP <1 mg/L) were determined. For each definition of REM, the mean change in each of the respective component scores was also assessed. Binary endpoints are based on Non-responder imputation (NRI), and continuous endpoints on mixed-effect model repeat measurement (MMRM). Comparisons were made between UPA-treated groups vs respective control arms (MTX, adalimumab [ADA] or PBO). Results: Patient demographics and disease characteristics have been previously reported. 1-3 At 12 weeks, in EARLY and COMPARE, a significantly greater proportion of patients receiving UPA 15 mg or 30 mg QD achieved REM by all 4 definitions vs MTX, PBO or ADA (Table). In BEYOND, (a refractory population many of whom had inadequate response to multiple bDMARDs), a significantly greater proportion of patients receiving UPA 30mg achieved all REM definitions vs PBO within the first 12 weeks, with significantly greater proportions on UPA 15mg achieving DAS28-CRP<2.6 and Boolean REM. Rates of REM in BEYOND further increased through Wk 24 for both dose groups. Compared to respective control groups, patients receiving UPA 15 or 30 mg QD had significantly greater improvements in each REM disease component (except for PhGA vs ADA in COMPARE). Significantly more patients receiving UPA also achieved the required cutoffs on the individual components of Boolean REM compared to respective controls. Conclusion: Significantly greater proportions of patients receiving UPA 15 or 30mg achieved REM by multiple definitions at 12 weeks compared to PBO, MTX or ADA. All disease activity components of each REM definition were significantly improved in patients receiving UPA compared to MTX or PBO, and all Boolean components were significantly improved in patients receiving UPA 15mg compared to ADA. Disclosures: S. Hall: Grants/research support; AbbVie, BMS, Lilly, Janssen, Pfizer, UCB, Novartis. T. Takeuchi: Honoraria; Mitsubishi-Tanabe Pharma Corp, Janssen Pharma KK, Chugai Pharma, Astellas Pharma Inc., AbbVie GK, Eisai Co., Ltd, BMS, Daiichi Sankyo Company Ltd, Eli Lilly Japan KK, Pfizer Japan Inc. Grants/research support; Pfizer Japan Inc., Eisai Co., Ltd, Astellas Pharma Inc., AbbVie GK, Asahi Kasei Pharma Corp, Nippon Kayaku Co., Ltd, Taisho Toyama Pharma, Takeda Pharma, AYUMI Pharma, Takahashi Industrial. G. Thomson: Consultancies; Amgen. Grants/research support; AbbVie. P. Emery: Grants/research support; Research grants and consulting fees from Pfizer, MSD, AbbVie, Bristol-Myers Squibb, UCB, Roche, Novartis, Samsung, Sandoz and Lilly. B. Combe: Grants/research support; Consultancy fees from Abbvie, BMS, Jansen, Lilly, MSD, Pfizer, Roche Chugai, UCB. A. Everding: None. K. Pavelka: Honoraria; Honoraria for lectures and consultations from companies: Pfizer, MSD, BMS, UCB, Amgen, Egis, Roche, AbbVie. Y. Song: Corporate appointments; Employee of AbbVie. T. Shaw: Corporate appointments; Employee of AbbVie. A. Friedman: Corporate appointments; Employee of AbbVie. I. Song: Corporate appointments; Employee of AbbVie. E. Mysler: Grants/research support; Research grants and consulting fees from AbbVie, Lilly, Pfizer, Roche, BMS, Sandoz.